2010
DOI: 10.1002/ejoc.201001368
|View full text |Cite
|
Sign up to set email alerts
|

Multidentate Pyridyl‐Based Ligands in the Coordination‐Driven Self‐Assembly of Palladium Metallo‐Macrocycles

Abstract: In the current study, a convenient way is presented to synthesize one ditopic and two tetratopic pyridine-based ligands, which are then used to construct metallo-supramolecular polygons. The tetratopic ligands offer two different metalbinding sites, one central 2,2Ј-bipyridine, which can act as a chelate ligand, and two separate pyridine rings, which mediate assembly formation. The three ligands differ with respect to their conformational flexibility. While a biphenyl core allows the ligand to adjust its confo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 99 publications
3
3
0
Order By: Relevance
“…These results suggested the difference between 3 and 1 was that 3 contained a (3-ethynyl)phenylamino moiety instead of a phenylamino moiety. The (3-ethynyl)phenylamino moiety in 3 was further confirmed by HMBC experiment ( Figure 2 and Supplementary Materials ) and comparison of 1 H-NMR and 13 C-NMR data with published data of (3-ethynyl)phenylamino moiety in literatures [ 7 , 8 ]. Thus, compound 3 was identified as a new (3-ethynyl)phenylamine-incorporated angucyclinone analogue.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…These results suggested the difference between 3 and 1 was that 3 contained a (3-ethynyl)phenylamino moiety instead of a phenylamino moiety. The (3-ethynyl)phenylamino moiety in 3 was further confirmed by HMBC experiment ( Figure 2 and Supplementary Materials ) and comparison of 1 H-NMR and 13 C-NMR data with published data of (3-ethynyl)phenylamino moiety in literatures [ 7 , 8 ]. Thus, compound 3 was identified as a new (3-ethynyl)phenylamine-incorporated angucyclinone analogue.…”
Section: Resultssupporting
confidence: 68%
“…Compound 3 was obtained as green-yellow solid, UV (MeOH) λ max (log ε): 272 (5.17), 358 (5.13) 1. The 1 H-NMR and 13 C-NMR spectra of 3 resembled that of 1, except that the resonances at δ 2 and Supplementary Materials) and comparison of 1 H-NMR and 13 C-NMR data with published data of (3-ethynyl)phenylamino moiety in literatures [7,8]. Thus, compound 3 was identified as a new (3-ethynyl) 13 C NMR (150 MHz, DMSO-d 6 ) data, Table 1.…”
Section: Structural Elucidation Of 3-6mentioning
confidence: 62%
“…A series of papers have documented the palladium/platinum driven assembly of metallocycles based on the related ligands L 1-4 . [1][2][3] In an initial communication it was shown that, as expected, when L 1 is reacted with two equivalents of [(dppp)Pd(OTf) 2 ], the tetranuclear M 4 L 2 metallocycle, [(dppp) 4 Pd 4 (m-Z 1 -Z 1 -Z 2 -L 1 )](OTf) 8 , results. 1 However, rather more surprising when just one equivalent of [(dppp)Pd(OTf) 2 ] was used, the selective coordination to the pyridyl sites at the expense of the bipyridyl moiety, leading to the formation of dinuclear M 2 L 2 metallocycle, [(dppp) 2 Pd 2 (m-Z 1 -Z 1 -L 1 )](OTf) 4 , was observed.…”
Section: Cyclic Oligomers (Metallocycles)supporting
confidence: 52%
“…[1][2][3] In an initial communication it was shown that, as expected, when L 1 is reacted with two equivalents of [(dppp)Pd(OTf) 2 ], the tetranuclear M 4 L 2 metallocycle, [(dppp) 4 Pd 4 (m-Z 1 -Z 1 -Z 2 -L 1 )](OTf) 8 , results. 1 However, rather more surprising when just one equivalent of [(dppp)Pd(OTf) 2 ] was used, the selective coordination to the pyridyl sites at the expense of the bipyridyl moiety, leading to the formation of dinuclear M 2 L 2 metallocycle, [(dppp) 2 Pd 2 (m-Z 1 -Z 1 -L 1 )](OTf) 4 , was observed. The same result was also observed starting with the analogous [(dppp)Pt(OTf) 2 ], however, rather subtly, changing the corner-capping bis(phosphine) altered this behaviour such that when [(dppe)M(OTf) 2 ] (M = Pd, Pt) was used, the metal centre is no longer able to discriminate between monodentate and bidentate sites.…”
Section: Cyclic Oligomers (Metallocycles)supporting
confidence: 52%
“…The synthesis of the ligand, which bears a bidentate 2,2 0 -bipyridine core and two terminal monodentate pyridine coordination sites, has recently been reported together with the formation of homometallic M : L = 4 : 2 complexes. 8 Interestingly, the addition of only 1 eq. of 2 resulted in a strongly preferred binding of the metal to the pyridine sites: In marked contrast to a previously reported quaterpyridyl ligand lacking the ethinylene spacers, 9 2 : 2 metallo-macrocycles form in a 1 : 1 mixture of 1 and 2.…”
mentioning
confidence: 99%